The Actual Condition of Establishment and Practice of Urban Transportation Planning in France (PDU): For an Example about Agglomeration Orleanaise - HARATA, Noboru; ITAYA, Kazuya (INFRASTRUCTURE PLANNING REVIEW, 2004)
In this paper, the relation between the planning, source of revenue, organization and agreement formation process was researched and that process explained the reason that the urban transportation plan in France has the actual effect The suggestions to our country by this are 1. to make the authority related to all the planning and management of the urban transportation, 2. to build the structure that many related subjects are involved in decision making, 3. to connect of the source of revenue system and the planning system. And to make these assumptions in the policy decision as a system in the whole of the country, is needed to raise the effect of the planning.